Analysis of Solid Medical Waste Management at X Hospital, West Sumatra - Puti Shakila Audhisa Israr; Nurul Mawaddah; Firdha Cahya Alam (Universitas Diponegoro, 2024)
X Hospital is one of the referral hospitals for handling COVID-19 patients, with 2,347 positive confirmed cases on November 12, 2021, which caused an increase in solid medical waste in 2022. Because solid medical waste has hazardous characteristics, there's an urgency to give more attention to potential risks. The impact can be reduced through proper waste management, starting with the waste stack. This study aims to identify sources and characteristics, waste stack, and implementation of solid medical waste management at X Hospital. This study uses quantitative and qualitative descriptive analysis, primary and secondary data collection, observation, interviews, and measurement of solid medical waste by SNI-19-3964-1994. The results found that solid medical waste originates with three characteristics of waste, the average stack generated is 56.53 kg/day, and the correlation between patients and solid medical waste obtained a Spearman rank correlation (r) value of 0.851 with a very strong correlation. Implementing solid medical waste management at X Hospital refers to applicable regulations with a percentage of good 80%. Sorting decomposing 82.5%, container 76%, collection 73%, storage 85%, and external transportation 100%. However, several indicators must be improved to comply with applicable regulations, especially minimization, container, collection, and storage.